Ask me anything: Joanne O'Meara. (December 2021) - Hiscott, Laura
Abstract : Joanne O'Meara is professor of physics at the University of Guelph, Ontario, Canada. She has a PhD in medical physics, and has done postdoctoral research at Tufts University and the Massachusetts Institute of Technology. Her outreach activities frequently include shows for schoolchildren and short segments on physics for the TV show Daily Planet.